Pengaruh Lingkungan Kerja, Motivasi Kerja, dan Kompensasi Kerja terhadap Produktivitas Kerja Karyawan PT Madu Baru Bantul - Heldianto, Savenda Tenma; Septyarini, Epsilandri; Purnamarini, Tri Ratna (Ekonomis: Journal of Economics and Business, 2025)
The aim of this research is to determine the influence of the work environment, motivation and compensation on employee work productivity at PT Madu Baru Bantul. The population and sample used were all 80 employees of PT Madu Baru Bantul using the saturated sampling method. Data obtained from the questionnaire was then processed and analyzed using multiple linear regression analysis. The research results show that simultaneously and partially there is a positive and significant influence between work environment variables, motivation and work compensation on the work productivity of PT Madu Baru Bantul employees.